2006
DOI: 10.6028/nist.sp.800-63v1.0.2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic authentication guideline

Abstract: Certain commercial entities, equipment, or material may be identified in the document in order to describe an experimental procedure or concept adequately. Such identification is not intended to imply recommendation or endorsement by the National Institute of Standards and Technology, nor is it intended to imply that these entities, materials, or equipment are necessarily the best available for the purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 0 publications
0
74
1
1
Order By: Relevance
“…To place this time in context, we compare it to Forget et al [9], who reported login times for 8-character text passwords as well as Persuasive Text Passwords (PTPs). 2 In the PTP variant that provided the optimal combination of security and usability, the login time was 17.1 sec. ; in this variant, users must memorize two extra characters in addition to their password.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To place this time in context, we compare it to Forget et al [9], who reported login times for 8-character text passwords as well as Persuasive Text Passwords (PTPs). 2 In the PTP variant that provided the optimal combination of security and usability, the login time was 17.1 sec. ; in this variant, users must memorize two extra characters in addition to their password.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…For a rough comparison, by NIST's historical password entropyestimation heuristics [2], assuming a 94-character alphabet (common printable characters excluding space), a 12-character user-chosen text password has about 24 bits of entropy: 4 bits for the first character, 2 each for the next 7, and 1.5 each for the last 4. If policy requires both uppercase and special characters, this rises to 30 bits; cf.…”
Section: Entropy Of Obpwd Password (Default Settings)mentioning
confidence: 99%
“…In NIST standard [4], we see four axis for evaluating authentications. In this paper, we borrow related two axes of evaluation: levels of initial identification (more generally, ID lifecycle management in [17,18]), and levels of tokens.…”
Section: Definitionmentioning
confidence: 99%
“…Generally, they are called "level of assurance (LoA)." There are defined some standards of LoAs such as NIST 800-63 [4] for evaluating the levels. In such situations, an SP(service provider) requires an appropriate LoA to an IdP(ID provider) for accessing its information assets.…”
Section: Stratified Paths Depending On Loamentioning
confidence: 99%
See 1 more Smart Citation